A study of Béla Tarr’s film aesthetics based on Heidegger’s phenomenology / Fauzi Naeim Mohamed - Fauzi Naeim , Mohamed (2017)
Béla Tarr is one of the most renowned filmmaker today who is famous for his long take aesthetics. All of his films display acute sense of societal alienation, bleak landscapes and temporal oppression. This dissertation analyzes Tarr’s later films [comprising from Damnation (1988), Sátántangó (1994), Werckmeister Harmonies (2000), The Man from London (2007) and A Turin Horse (2011)] according to Heideggerian phenomenology. Martin Heidegger (1889-1976), a German philosopher, is famed for his study of the ontology of Being (Sein) in Being and Time (Sein und Zeit, 1927/1962). His ideas on Dasein (Being-there), is considered as a groundbreaking contribution in hermeneutic phenomenology. This dissertation elaborate on Béla Tarr’s aesthetics from the analysis of Heidegger’s later works; interrogating the phenomenology of lingering shot, art and truth in film, the mode of nothingness, cinematic boredom, dwelling in cinema, metaphysics of nihilism and essence of Being. This dissertation argue that Béla Tarr’s long take discloses the essence of Being, which runs parallel to Heidegger’s quest in understanding the essence of Being in his philosophy, which asks for a thoughtful retrospection of the meaning of existence. The dissertation conclude that Béla Tarr’s long take films offer distinctive ways to thinking and contemplating Being.